Teaching entrepreneurship to undergraduates - Jones, Colin (Cheltenham, UK : Edward Elgar, 2011)
The book provides a unique and superior conceptualization of entrepreneurship education, creating a more student-centric approach to learning, not a lecturer-centric approach to teaching.
Foreword / Allan Gibb -- Your teaching philosophy -- Entrepreneurship education -- The ontological dilemma -- The reasonable adventurer -- Student diversity -- The learning environment -- The resource profile -- The art of selling -- Evaluating ideas -- Business plans -- Accounting for interaction.
Includes bibliographical references (p. 158-163) and index.
oif 23/05/13
Loan
Keywords: Entrepreneurship -- Study and teaching (Higher)